Variations in peak nasal inspiratory flow among healthy students after using saline solutions - Olbrich Neto,Jaime (2016)
ABSTRACT INTRODUCTION: Nasal hygiene with saline solutions has been shown to relieve congestion, reduce the thickening of the mucus and keep nasal cavity clean and moist. OBJECTIVE: Evaluating whether saline solutions improve nasal inspiratory flow among healthy children. METHODS: Students between 8 and 11 years of age underwent 6 procedures with saline solutions at different concentrations. The peak nasal inspiratory flow was measured before and 30 min after each procedure. Statistical analysis was performed by means of t test, analysis of variance, and Tukey's test, considering p < 0.05. RESULTS: We evaluated 124 children at all stages. There were differences on the way a same concentration was used. There was no difference between 0.9% saline solution and 3% saline solution by using a syringe. CONCLUSION: The 3% saline solution had higher averages of peak nasal inspiratory flow, but it was not significantly higher than the 0.9% saline solution. It is important to offer various options to patients.